Zmiana sytuacji gospodarczej nowych państw członkowskich Unii Europejskiej - Stawicka, Magdalena Kinga (The Change of Economic Situation in New Member States of the European Union, 2008)
On May 1st 2004, after a long-term period of preparations ten new European countries became rightful members of an economic and political community namely the European Union. The purpose of the article is a comparison of new European Union countries in the aspect of macro economical indexes as well as an examination of modifications which took place after they had joined the European Union. The following indexes were used in the analysis real gross domestic product growth rate, gross domestic product per an inhabitant, general unemployment rate, inflation rate, public balance and foreign direct investment per capita.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 155-166